KINERJA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN LOMBOK TIMUR DALAM PEMBENTUKAN PERATURAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 - WIDIANI, HELMI (Fakultas Hukum Universitas Gunung Rinjani, 2021)
In the 1945 Constitution of the Republic of Indonesia, it was mandated that the regional government has the authority to regulate and manage its own affairs according to the principle of autonomy. Regions have the right to form their own legal products (Perda). The DPRD has three functions, one of which is the function of legislation, namely the function of making regional regulations with regional heads. The DPRD together with the Regional Government must form a good local regulation and in accordance with the conditions of the local community. In Lombok East Regency, the performance of the Lombok East DPRD is considered optimal in the formulation of regional regulations Qualitative research approach. Type of empirical juridical research. Research location of the Lombok East Regency DPRD building. Data collection using interviews and documentation. Data processing techniques use descriptive methods. The conclusions of this study are Lombok East Regency DPRD in the process of drafting the Lombok East Regency Regulation, it can be concluded that the performance of the Lombok East Regency DPRD in the process of drafting the Regional Regulation has not gone well, because of the 5 aspects used in the field to become analysis